Community Attitude Towards the Impact of the Relocation of Settlements Along the Karang Mumus River - Saidi, Arbainah; Habibi, Muhammad (PINISI Discretion Review, 2025)
This study aimed to analyze and determine the success of the government program in the community's attitudes toward the relocation of settlements along the Karang Mumus River in Pelita Village, Samarinda City. To obtain accurate answers, this study focused on the cognitive, affective, and conative components of community attitudes toward the impact of the relocation of settlements along the Karang Mumus River in Pelita Village, Samarinda City. The research used a descriptive qualitative approach, aiming to describe and explain the phenomena in depth. The interactive model of Miles and Huberman (1994) was used for data analysis. The data analysis revealed that the community's attitudes toward the relocation were cognitively accepting all government regulations regarding the relocation of their settlements (professional) and taking responsibility for their own actions. The community's affective attitudes were characterized by feelings of sadness and disappointment, as well as joy. The sadness stemmed from leaving a place filled with memories and a place where they could live comfortably. The disappointment stemmed from not receiving adequate financial assistance from the government for the building they occupied. In terms of community attitudes, feelings of sadness, disappointment, and happiness regarding the relocation program implemented by the Samarinda City government are limited to feelings regarding property rights or housing, not concrete actions. This is evident in the success of the relocation program in Pelita Village, located in neighborhood units (RT) 41, 42, and 43.